Women in Urban Fire Disaster Mitigation: A Bibliometric Analysis of Research Trends, Intellectual Structure, and Thematic Evolution (2016–2025: . - Ari Sulistyanto; Pagi Muhamad; Rr Dinar Soelistyowati (HUMAN: Journal of Social Humanities and Science, 2026)
Urban fire disasters remain a major challenge for disaster risk reduction in densely populated cities. Women play important roles in preparedness, response, and community resilience, yet studies examining their contributions remain fragmented across different research themes. This study aims to map the development of scientific publications on women in urban fire disaster mitigation and identify publication trends, influential authors, collaboration networks, and thematic evolution. The study employed a bibliometric approach using Scopus as the primary database. Publications published between 2016 and 2025 were retrieved through a systematic search and screened using the PRISMA framework. The dataset was analyzed with Bibliometrix and VOSviewer to examine annual publication trends, author productivity, co-authorship networks, keyword co-occurrence, overlay visualization, and density visualization. The findings indicate that scientific publications have increased during the study period, reflecting growing academic interest in women's roles in urban fire disaster mitigation. Several leading authors and collaborative research networks have contributed to shaping this research field. Keyword analysis reveals that recent studies increasingly emphasize gender, fire safety, emergency evacuation, disaster preparedness, risk communication, and community capacity building. These findings demonstrate a shift from vulnerability-oriented perspectives toward more inclusive approaches that recognize women as active contributors to disaster risk reduction. This study provides a comprehensive overview of the intellectual structure and thematic development of the field while offering valuable references for future research and evidence-based policies promoting gender-inclusive urban fire disaster mitigation.